(untitled) (International Journal of Current Engineering and Technology, 2014)
Investigations were carried out to study exhaust emissions of a medium grade low heat rejection (LHR) diesel engine with an air gap insulated piston and air gap insulated liner with different operating conditions [normal temperature and pre-heated temperature] of cotton seed biodiesel with varied injector opening pressure and injection timing. Exhaust emissions of particulate emissions and nitrogen oxide (NOx) levels were evaluated at different values of brake mean effective pressure (BMEP) of the engine. Comparative studies were made with conventional engine (CE) with biodiesel and also with mineral diesel operation with similar working condition. Particulate emissions decreased while NOx levels increased with engine with LHR combustion chamber with biodiesel in comparison with CE.